EP013/#933 Testing for mismatch repair protein deficiency, microsatellite instability, and lynch syndrome in ovarian cancer: a systematic review and meta-analysis. (4th December 2022) - Mitric, Cristina; Salman, Lina; Kim, Soyoun Rachel; Gien, Lilian; Ferguson, Sarah
Abstract : Objectives: Identifying Lynch syndrome (LS) in endometrial cancer through reflex tumour testing for mismatch repair protein deficiency (MMRd) and microsatellite instability (MSI) is widely accepted, but knowledge is limited about its value in ovarian cancer. The current systematic review and meta-analysis evaluated the prevalence of MMRd, MSI-high, and LS in ovarian cancer, as well as the tests performance characteristics. Methods: We systematically searched the MEDLINE, Cochrane Central Register of Controlled Trials, and Embase databases from inception until February 2022. We included studies assessing MMRd using immunohistochemistry (IHC), MSI, and/or germline LS by next-generation sequencing (NGS). Results: A total of 45 studies were included. The incidence for MMRd was 9% (95% CI 6–14%), MSI-high 12% (12–15%), and LS 5% (2–14%) in all epithelian ovarian cancer respectively. Hypermethylation was identified in 77% (95% CI 63–87%) of those with MLH1 deficiency. MMR IHC for LS diagnosis has 92% sensitivity, 77% specificity, 58% positive predictive value, and 98% negative predictive value, whereas MSI performance characteristics were 97%, 91%, 25% and 77% respectively. Synchronous ovarian and endometrial cancers had highest rates of MMRd (26%) and MSI-H (34%). Serous histology had lowest prevalence of 1% for MMRd and 7% for MSI. The highest prevalence of germline pathogenic variants in MMR genes (LS) were found in those with synchronous endometrial-ovarian cancer (53%) as well as clear cell ovarian cancer (25%) with the lowest prevalence in serous ovarian (1%) cancer. Conclusions: MMR deficiency, MSI, and LS are frequent in ovarian cancer, in particular in non-serous histological subtypes.